2014
DOI: 10.1007/s10517-014-2422-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Galectin-1 on Apoptosis of CD4+ Lymphocytes Differentiated In Vitro Towards Regulatory T Cells

Abstract: We studied the effect of galectin-1 on apoptosis of CD4(+) lymphocytes intact and in vitro differentiated towards regulatory T cells. An increase in the content of apoptotic CD4(+) lymphocytes was observed after exposure of intact cells with 15 ng/ml galectin-1 and after exposure of regulatory T cells with 10 and 15 ng/ml galectin-1. Apoptosis of regulatory T cells induced by galectin-1 was accompanied by an increase in the content of proapoptotic protein Bad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
3
1
0
1
Order By: Relevance
“…29 Gal-1 is one of the inducers of Treg. 30 The present data are in line with the previous studies by showing that as the serum levels of mast cell-derived mediators were still higher in mice treated with SIT. Other investigators also found that sensitized mast cells were activated to release Th2 cytokines on exposure to specific antigens in the culture.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…29 Gal-1 is one of the inducers of Treg. 30 The present data are in line with the previous studies by showing that as the serum levels of mast cell-derived mediators were still higher in mice treated with SIT. Other investigators also found that sensitized mast cells were activated to release Th2 cytokines on exposure to specific antigens in the culture.…”
Section: Discussionsupporting
confidence: 93%
“…To generate antigen‐specific Tregs is one approach to restore immune tolerance to alleviate immune disorders . Gal‐1 is one of the inducers of Treg . The present data are in line with the previous studies by showing that administration of Gal‐1 promoted the induction of antigen‐specific Tregs in the intestine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The molecule neuropilin-1 (Nrp-1) is also expressed at higher levels on Treg than naïve T helper lymphocytes; the interaction of this molecule with immature DCs results in prolonged contact and subsequently in antigen-specific Treg generation [68]. Direct Treg contact with Teff via galectin-1 [60, 69,70] and serine protease granzyme [60] can cause apoptosis or arrest of effector lymphocytes without working intermediately through DCs.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Los efectos de las galectinas sobre la síntesis de citocinas por las células T hacen que la secreción final determine la polarización de TH1/TH2 de la respuesta inmune. Mediante la reducción de IFN-γ y IL-2 y la producción aumentada de IL-5, IL-10 y TGF-β, la Gal-1 desvía el equilibrio de una respuesta TH1 polarizada hacia una respuesta TH2, mientras que al reducir los niveles de IL-5, la Gal-3 tiene el efecto opuesto (Yakushina et al, 2014).…”
Section: Las Galectinas En El Sistema Inmunológicounclassified